Gendered aspirations and occupation among rural youth in agriculture and beyond: a cross-regional perspective - Elias, Marlène (Bioversity International, 2018)
Presented by Marlene Elias (Bioversity International / GENNOVATE), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.